Analysis of risk factors associated with squamous cell carcinoma in the Indian population - Annasaheb J Dhumale; Sachin Mohite; Rathi Rela; Shahla khan; Wagisha Barbi; K A Ahamed Irfan; Priyadarshini Rangari (Wolters Kluwer Medknow Publications, 2021)
Background: Squamous cell carcinoma (SCC) describes the carcinomatous growth in the oral cavity. Recently, various authors have described increased SCC incidence in the young population. The distribution of SCC shows varied geographic spread, with the highest distribution in Asian countries. Aims: The present trial was carried out to assess the associated factors that could lead to increased risk of developing oral cancer. Materials and Methods: Oral examination was carried out for 21 participants by a dentist and any significant oral lesion or deleterious habit if present, was recorded. The data collected were analyzed. Results: Areca nut was chewed by 47.61% participants (n = 10), smoking tobacco by 76.19% (n = 16), chewing tobacco by 38.09% (n = 8), and consuming alcohol in 9 participants (42.85%). No significant difference was seen concerning age for any factor except alcohol which showed higher intake in the older group where six participants depicted alcohol intake as compared to three participants in the younger group. In participants who chewed areca nuts, 6 participants also smoked tobacco and 1 consumed alcohol. For tobacco chewing, 5 consumed alcohol and 6 also took tobacco as smoke. Conclusion: The present study showed that areca nut and tobacco chewing along with alcohol consumption and tobacco smoking increase the risk of developing SCC in the Indian population.